East of Delhi: multilingual literary culture and world literature - Orsini, Francesca (New Delhi OUP, 2023)
East of Delhi: Multilingual Literary Culture and World Literature examines literature produced, practiced, and circulated in and out of North India, focusing on the region of Awadh, from the beginning of recorded vernacular literature in the late fourteenth century to the colonial era of the early twentieth century. This book considers texts in a wide range of genres-courtly, devotional, and popular-composed in the main languages of the region: Hindavi, Persian, Brajbhasha, Urdu. Individual chapters focus on narratives, devotional song-poems and didactic works, local courtly literary practices, and multilingual education as recorded in biographical dictionaries-anthologies. Author Francesca Orsini suggests that this multilingual and multi-genre approach is better suited to capturing the texture, complexity, and dynamics of literature in the world, and of literary history, than approaches that focus only on global circulation or models that draw centers and peripheries on a single global map.
Keywords: Literature- East of Delhi; World Literature; Multilingual Literature